Appropriateness of frequent use of emergency departments: A retrospective analysis in Rome, Italy - Giuseppe Furia; Giuseppe Furia; Antonio Vinci; Antonio Vinci; Vittoria Colamesta; Paolo Papini; Adriano Grossi; Vittoria Cammalleri; Patrizia Chierchini; Massimo Maurici; Gianfranco Damiani; Corrado De Vito (Frontiers in Public Health, 2023)
BackgroundFrequent users (FUs) are patients who repeatedly and inappropriately visit the emergency department (ED) for low-grade symptoms that could be treated outside the hospital setting. This study aimed to investigate the phenomenon of the FU in Rome by profiling such users and analyzing ED attendance by FUs.MethodsThe analysis was carried out for attendance in 2021 at 15 EDs in the Local Health Authority Roma 1 geographical area. A digital app collected data, including information on the following variables: number of attendance, demographic characteristics, emergency medical service (EMS) usage, triage code, and appropriateness of attendance. COVID-19 diagnosis was also studied to analyze any possible influence on ED attendance. Differences between FUs and non-FUs were investigated statistically by t-test and chi-square test. Univariate analysis and multivariable logistic regression were performed to analyze the associated factors.ResultsA total of 122,762 ED attendance and 89,036 users were registered. The FU category represented 2.9% of all users, comprising 11.9% of total ED attendance. There was a three times higher frequency of non-urgent codes in attendance of FU patients (FU: 9.7%; non-FU: 3.2%). FUs were slightly more likely to have used the EMS (13.6% vs. 11.4%) and had a lower frequency of appropriate ED attendance (23.8% vs. 27.0%). Multivariate logistic analysis confirmed a significant effect of triage code, gender, age, EMS usage, and COVID-19 diagnosis for the appropriateness of attendance. The results were statistically significant (p < 0.001).ConclusionThe FU profile describes mostly non-urgent and inappropriate attendance at the ED, including during the COVID-19 pandemic. This study represents an important tool for strengthening preventive policies outside the hospital setting. The Italian National Recovery and Resilience Plan represents an excellent opportunity for the development of new strategies to mitigate the phenomenon of FUs.